Non-Antimicrobial Adjuvant Therapy Using Ticagrelor Reduced Biofilm-Related Staphylococcus aureus Prosthetic Joint Infection - Pant, Narayan; Miranda-Hernandez, Socorro; Rush, Catherine; Warner, Jeffrey; Eisen, Damon P. (Frontiers in Pharmacology, 2022)
Background: Prosthetic joint infection (PJI), frequently caused by Staphylococcus aureus, leads to a significant arthroplasty failure rate. Biofilm is a crucial virulence factor of S. aureus, that is intrinsic to the pathogenesis of PJI. Biofilm-related infections are recalcitrant to antibiotic treatment. Surgical and antibiotic therapy could be combined with non-antibacterial adjuvants to improve overall treatment success. Ticagrelor, a P2Y12 receptor inhibitor antiplatelet drug, is known to have anti-staphylococcal antibacterial and antibiofilm activity. However, the molecular mechanism for ticagrelor's antibiofilm activity and its efficacy in the treatment of S. aureus PJI are unknown. Methods: Ticagrelor's effect on the expression of S. aureus biofilm genes (icaA, icaD, ebps, fib, eno, agr) was studied using the relative quantification method. To test ticagrelor's in-vivo efficacy to treat S. aureus PJI, mice were randomized into five groups (n=8/group): infected femoral implants treated with ticagrelor alone; infected implants treated with cefazolin alone; infected implants treated with ticagrelor and cefazolin; infected implants treated with phosphate buffer solution (PBS)-positive controls and sterile implant-negative controls. Ticagrelor was administered orally from day 4 to day 7 post-surgery, while cefazolin was injected intravenously on day 7. Results: Ticagrelor, alone and with selected antibiotics, showed in-vitro antibacterial and antibiofilm activity against S. aureus. Strain-specific downregulation of biofilm-related genes, fib, icaD, ebps, and eno, was shown. In an animal model of biofilm-related S. aureus PJI, ticagrelor alone and combined with cefazolin significantly reduced bacterial concentrations on the implants in comparison with the positive control group. Ticagrelor significantly reduced bacterial dissemination to the periprosthetic tissue compared with the positive controls. Conclusion: Biofilm dispersal using non-antimicrobial ticagrelor adjuvant therapy may improve the success rate of PJI treatment.